Limit State of Bake Hardened Stamped Interstitial-free Steel Automotive Parts Caused by Local Thickness Reduction - Klejch, Filip; Schmidová, Eva (Periodica Polytechnica Transportation Engineering, 2024)
Current trends in the complex shapes of modern automobiles lead to the need for extremely formable materials for deep drawing applications. In general Interstitial–Free (IF) steels present the solution for this purpose. In addition, the cold stamping process is influenced by a variety of input factors that must be correctly adjusted. An imperfection in one of the inputs may cause stamping defects even with deep drawing materials. Limit states may then appear in the form of cracks or unacceptable thinning in the critically stressed areas of the stamped parts. For this reason, a general focus is placed on the use of non-destructive methods and inspection of stamped parts after stamping for potential subsequent modification of the stamping process. The presented work deals with the material analyses of stamped parts made of Bake-Hardened Interstitial-Free steel, including the local thickness reduction of the material, leading to the occurrence of crack propagation. The focus of the work was placed on the critical influencing factors resulting from the limit states presented. The evaluation of the material flow and the local plastic response was carried out using a cylindrical indentation method. In addition, the SEM analyses showed the importance of the deformation capacity of the surface coating which proved to be one of the decisive parameters for the occurrence of limit states.